Análise da influência da geometria em um trocador de calor compacto tubo-aleta através de simulação - Krubniki, Larissa Ruppert (2016)
This study performed a computer simulation of heat transfer by forced-convection in a tube-fin heat exchanger with different geometries of fins, which are plates, annular, pitman, verticals and a heat exchanger without fins. The results show that the use of fins makes the most effective heat exchange tubes and compared with annular fins proved to be more efficient.